A Nanoplastic Sampling and Enrichment Approach by Continuous Flow Centrifugation - Hildebrandt, Lars; Mitrano, Denise M.; Zimmermann, Tristan; Pröfrock, Daniel (Frontiers in Environmental Science, 2020)
Substantial efforts have been undertaken to isolate and characterize plastic contaminants in different sample matrices in the last years as the ubiquitous presence of particulate plastic in the environment has become evident. In comparison, plastic particles < 1 µm (nanoplastic) in the environment remain mostly unexplored. Adequate techniques for the enrichment, as well as the detection of nanoplastic, are lacking but are urgently needed to assess the full scope of (potential) nanoplastic pollution. Use of Pd-doped nanoplastic particles constitutes a powerful tool to develop new analytical approaches, as they can be traced accurately and with ease in a variety of complex matrices by highly sensitive, time-efficient and robust ICP-MS(/MS) techniques. In this lab-scale study, for the first time, the capability of continuous flow centrifugation to retain nanoplastic particles (~ 160 nm) from ultrapure water, as well as from filtered and unfiltered water from the German Elbe River was evaluated. Depending on the pump rate, the retention efficiency for the nanoplastic particles in ultrapure water ranged from 92% ± 8% (1 L h-1) to 53% ± 5% (5 L h-1) (uc (n = 3)) and from 75.3% ± 2.8% to 65% ± 3% (uc) in river water. Recirculating the water through the system two and three times at the highest tested flow rate led to retention efficiencies > 90%. In a proof-of-principle setup, it was demonstrated that operating two continuous flow centrifuges sequentially at different rotational speeds bears the potential to enable size- and density-selective sampling of the colloidal fraction. A significant fraction of the spiked nanoplastic particles (76% ± 5% (uc)) could be separated from a model mixture of natural particles with a well-defined mean size of approximately 3 µm. While the certified reference plankton material used here was quantitatively retained in the first centrifuge rotor together with 23.0% ± 2.2% of the effective dose of the spiked nanoplastic, the remaining fraction of the nanoplastic could be recovered in the second rotor (53% ± 5%) and the effluent (24.4% ± 2.4% (uc)). Based on the good retention